Influence of Lactobacillus and Bifidobacterium on interferonogenesis and phagocytic cells activity - Spivak, Mykola; Pidgorsky, Valentin; Lazarenko, Lyudmila; Shynkarenko, Lyubov; Rachkova, L. T.; Olevinska, Zoya; Timoshok, Natalia; Starovoitova, Svitlana (My University, 2009)
It was established that Bifidobacterium bifidum, Bifidobacterium longum, Lactobacillus acidofilus, Lactobacillus casei, Lactobacillus bulgaricus as well as standard interferon inducer ridostine in vivo had activating influence on production of endogenous interferon that proved to be true by essential increase of interferon titer in blood serum of mice during 6 days. For 12 days the interferon titer in blood serum did not exceed a control value. Lactobacillus acidofilus and Bifidobacterium longum have appeared the most effective inducing agent of both “early” and “late” interferon. The simultaneous injection of Bifidobacterium bifidum, Bifidobacterium longum, Lactobacillus acidofilus, Lactobacillus casei, Lactobacillus bulgaricus led to more significant increase of interferon titer in mic blood serum comparing with the influence of the single strain.
Keywords: interferonogenesis; phagocytosis system cells; Lactobacillus; Bifidobacterium; інтефероногенезіс; клітини фагоцитарної системи; Lactobacillus; Bifidobacterium; интерфероногенезис; клетки фагоцитарной системы; Lactobacillus; Bifidobacterium; кафедра біотехнології і мікробіології